Amino/guanidino-functionalized N-(pyrrolidin-2-ethyl)glycine-based pet-PNA: design, synthesis and binding with DNA/RNA - Gokhale, Sachin S.; Kumar, Vaijayanti A. (Organic & Biomolecular Chemistry, 2010)
The N-(pyrrolidin-2-ethyl) glycine-based PNA (pet-PNA) backbone, with 4-amino or 4-guanidino-functionalized pyrrolidine ring, confers constrained conformational flexibility on aegPNA. The oligomers bind to the target DNA and RNA sequences with increased sequence specificity and antiparallel versus parallel orientation selectivity. The easy post-synthetic guanidination gives very good access to the positively charged PNA oligomers.